LncRNA‐ATB mediated E‐cadherin repression promotes the progression of colon cancer and predicts poor prognosis. Issue 3 (26th February 2016) - Yue, Ben; Qiu, Shenglong; Zhao, Senlin; Liu, Chenchen; Zhang, Dongyuan; Yu, Fudong; Peng, Zhihai; Yan, Dongwang
Abstract: Background: Long non‐coding RNA‐activated by TGF‐β (lncRNA‐ATB) promotes the invasion–metastasis cascade in hepatocellular carcinoma via downregulating E‐cadherin (E‐cad) and inducing epithelial‐to‐ mesenchymal transition (EMT) and is clinically significant in human colon cancer. However, its molecular mechanisms in colon cancer progression remain unclear. This study aimed to elucidate the role of lncRNA‐ATB and its clinical value in colon cancer. Methods: Expression levels of lncRNA‐ATB in colon cancer tissues and colon cancer cell lines were evaluated using quantitative real‐time polymerase chain reaction. The clinicopathological significance and prognostic value of lncRNA‐ATB were investigated, and roles of lncRNA‐ATB in regulating E‐cad and other EMT‐related markers expression and colon cancer progression were evaluated in vitro . Expression levels of lncRNA‐ATB and E‐cad in human plasma were evaluated. Results: Long non‐coding RNA‐activated by TGF‐β was upregulated in colon cancer tissues compared with adjacent mucosa ( P < 0.001). LncRNA‐ATB levels were also higher in metastatic cancer tissues ( P < 0.001). Among the three highly invasive colon cancer cell lines, lncRNA‐ATB levels were relatively higher with concurrent low levels of E‐cad compared with levels in the three low‐invasive cell lines. LncRNA‐ATB expression correlated with pN stage ( P < 0.01) and American Joint Committee on Cancer stage ( P < 0.01). Striking differences were observed in overall survival and disease‐free survival in cases with both high lncRNA‐ATB expression and low E‐cad expression. Reduction of lncRNA‐ATB increased expression of epithelial markers E‐cad, ZO‐1, and decreased expression of mesenchymal markers ZEB1 and N‐cadherin (N‐cad), and significantly influenced colon cancer cell progression. Plasma lncRNA‐ATB was upregulated in colon cancer patients one month after surgery ( P < 0.05). Conclusions: Long non‐coding RNA‐activated by TGF‐β may act on colon tumorigenesis by suppressing E‐cad expression and promoting EMT process, and lncRNA‐ATB inhibition may provide a promising therapeutic option for suppressing colon cancer progression.